Nationwide survival after inhospital cardiac arrest before and after 2010 cardiopulmonary resuscitation guidelines: 2007–2014. (15th December 2017) - Mallikethi-Reddy, Sagar; Akintoye, Emmanuel; Rubenfire, Melvyn; Briasoulis, Alexandros; Grines, Cindy L.; Afonso, Luis
Abstract: Background: American Heart Association has been revising the cardiopulmonary resuscitation (CPR) guidelines quinquennially. We sought to study the influence of 2010 CPR guidelines on nationwide survival after inhospital cardiac arrest. Methods: Healthcare Utilization Project's National Inpatient Sample 20007-2014, was used to identify 799, 741 adults aged ≥ 15 years, who underwent inhospital CPR. We compared inhospital survival trends during period before (2007–2010) and after (2011–2014) American Heart Association 2010 CPR guidelines. Results: Mean age of the study population was 66.5 years. Females constituted 44% of the study cohort. There was a significant improvement in survival after inhospital CPR from 24.1% in 2007 to 31.1% in 2014 ( P trend  < 0.001). However, we did not find any statistically significant improvement in inhospital survival after CPR, in the study period after 2010 AHA CPR guidelines in comparison to study period before the guidelines. Conclusions: We noted a significant improvement in inhospital survival rate after CPR from 2007 through 2014 in the United States, though there was no statistically significant improvement in survival trends after 2010 CPR guidelines during period 2011–2014, in comparison to period 2007–2010.